2015
DOI: 10.1371/journal.pone.0122018
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Fibrinolysis by a Sequential Synergistic Combination of Mini-Dose tPA plus Low-Dose Mutant proUK

Abstract: Results of thrombolysis by monotherapy with either tPA or proUK have not lived up to expectations. Since these natural activators are inherently complementary, this property can be utilized to a synergistic advantage; and yet, this has undergone little evaluation. ProUK is no longer available because at pharmacological concentrations it converts to UK in plasma. Therefore, a single site proUK mutant, M5, was developed to address this problem and was used in this study. Fibrinolysis was measured using preformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…These fractional doses were almost identical to those of tPA and proUK in the clinical PATENT trial, which were 5 and 40 %, as described above. This similarity between the findings from this in vitro study to those found clinically provided evidence for the clinical relevance of the clot lysis model [ 56 ].…”
Section: Mutant Prouk (Hisprouk)supporting
confidence: 79%
“…These fractional doses were almost identical to those of tPA and proUK in the clinical PATENT trial, which were 5 and 40 %, as described above. This similarity between the findings from this in vitro study to those found clinically provided evidence for the clinical relevance of the clot lysis model [ 56 ].…”
Section: Mutant Prouk (Hisprouk)supporting
confidence: 79%
“…However, the difference between tPA-PEG-cRGD-lip and free tPA was not considerable (approximately 15%). This is probably because the clot lysis induced by tPA is a gradual process, as reported by other researchers [57,58]. However, after 75 min of treatment when majority of tPA was released from tPA-PEG-cRGD-lip ( Figure 4B), the liposomal tPAs, like free tPA, caused almost the complete blood clot lysis.…”
Section: Accepted Manuscriptmentioning
confidence: 51%
“…Because proUK's instability was unrelated to its fibrinolytic mechanism of action, this problem was addressed by site-directed mutagenesis, which improved its plasma stability fivefold without interfering with its mechanism of action. [22][23][24] By contrast, the bleeding side effects with tPA are primarily due to its lysis of hemostatic fibrin at vascular repair sites, 25,26 which is due to its therapeutic fibrinolytic mechanism of action.…”
Section: Clinical Significancementioning
confidence: 99%